Determinants of Anxiety in the General Latvian Population During the COVID-19 State of Emergency - Vrublevska, Jelena; Perepjolkina, Viktorija; Martinsone, Kristine; Kolesnikova, Jelena; Krone, Ilona; Smirnova, Daria; Fountoulakis, Konstantinos N.; Rancans, Elmars (Frontiers in Public Health, 2022)
Background: The rapid spread of COVID-19 and its restrictive public health measures have seriously affected the physical and mental well-being of society worldwide, and many social, psychological, and health-related factors have been linked to an increase in anxiety in the general population. Aim: We investigate the association of various sociopsychological and health-related determinants of anxiety and identify the predicting factors for anxiety in the general population during the COVID-19 state of emergency in Latvia. Methods: We conducted an online survey using a randomized stratified sample of the general adult population in July 2020 for three weeks. The statistical analysis included Pearson’s chi-square test and post hoc analysis that involved pairwise comparisons using the multiple z-test of two proportions with a Bonferroni correction. We used an independent samples t-test and a one-way ANOVA to analyze the mean differences of the continuous variables. We identified the predictors of anxiety using a binomial logistic regression. Results: The weighted study sample included 2,608 participants. The mean STAY-S score of the total sample was 22.88±12.25. In the total sample, 15.2% (n = 398) of participants were classified as having anxiety. The odds ratio (OR) of having anxiety was higher in females (OR = 2.44) and people who had experienced mental health problems in the past (OR = 1.45), had suicidal ideation in the past (OR = 1.68), were worried about their health status due to COVID-19 (OR = 1.64), were worried about stigmatization from others if infected with COVID-19 (OR = 1.18), were worried about information regarding COVID-19 from the Internet (OR = 1.24), persons who were lonely (OR = 1.90), and persons with negative problem orientation (OR = 1.26). Protective factors were identified as having good self-rated general health, maintaining a daily routine, having financial stability, and having good psychological resilience. Conclusions: The results highlight the importance of (1) identifying and supporting those who are at risk to alleviate suffering in future possible lockdowns, and (2) providing the community with the necessary psychological support to reduce anxiety.